Estrutura e funcionamento de comunidades biológicas em ecossistemas fragmentados - Schuh, Marina Habkost (2013)
The recognition of patterns in community structure and the elucidation of the processes responsible for variation in species richness among habitats that produce these patterns are classical goals of community ecology. The nestedness pattern of species occurrence on islands was initially postulated as resulting from selective extinction - species-poor sites are subsets of species-rich sites. Alternative mechanisms that can generate this pattern include passive sampling, selective extinction, selective colonization and habitat nestedness. The concept, measures and analysis strategies of nestedness have recently been challenged by studies demonstrating the inconsistency of approaches traditionally used, so the issue remains open. This study investigated the nestedness of waterbirds assemblages in fragments of wetlands and their mechanisms responsible. Specifically, the following expectations were tested: (1) the nestedness pattern is associated with the nestedness habitat, related to the size of the fragments; (2) the nestedness pattern is not related to the isolation of the fragments; (3 ) the species that deviate from the nestedness pattern present biological attributes associated with vulnerability to habitat loss; (4) the fragments that deviate from the nestedness pattern present a peculiar structure of microhabitats, not related to the internal heterogeneity of microhabitats. We conducted 12 monthly census of birds over one year, from January to December 2003. Were obtained values corresponding to the area of 42 fragments, proximity index and richness of microhabitats through Landsat images and aerial photographs. Matrixes of presence and absence were ordered by species richness, incidence of species, fragments area, proximity index, microhabitats richness and correspondence analysis. All ordinations resulted in nested pattern, with the area and the diversity of microhabitats primarily responsible for generating the standard nested. It was also found nestedness habitat in the fragments analyzed. Idiosyncratic species are the most frequent and generalists. The species with the highest occurrence have larger body size, less selectivity in the diet and less sensitive to disturbance. Considering these factors and the importance of the area in the generation of the nestedness, nesting species appears to result from a number of factors that interact and contribute to this pattern, and the results are consistent with the hypothesis of selective extinction and colonization, and nesting habitats. Furthermore, it can be inferred that appropriate conservation measures for this region should prioritize the preservation of large fragments in microhabitats that are added to the system, facilitating the addition of other species to the assembly.